Multiple thrombosis associated with Cytomegalovirus enterocolitis in an immunocompetent patient: a case report - Kaisei Kamatani; Tsuneaki Kenzaka; Ryu Sugimoto; Ayako Kumabe; Akihito Kitao; Hozuka Akita (BMC Infectious Diseases, 2021)
Abstract Background Cytomegalovirus (CMV) is reported to have thrombogenic characteristics that activate factor X in vitro and stimulate the production of factor VIII and von Willebrand factor (vWF). Thrombosis associated with CMV infection is prevalent among immunocompromised patients and predominantly presents as a solitary large thrombus in the deep vein, pulmonary artery, splanchnic arteriovenous ducts, or other similar sites. Multiple thrombi, however, are rarely observed in such cases. Here, we report about an immunocompetent man with multiple microthrombi associated with CMV infection. Case presentation A 72-year-old Japanese man who complained of abdominal pain was hospitalized with multiple colonic stenosis. He was later diagnosed with CMV enterocolitis and treated with ganciclover from Day 27 post-admission. During hospitalization, the patient developed thrombi in his fingers. He was initially treated with anticoagulant therapy (rivaroxaban); however, the therapy was discontinued owing to a prolonged activated thromboplastin time and an elevated international normalized ratio of prothrombin time. Instead, vitamin K and fresh-frozen plasma were administered. Nevertheless, his coagulation profile remained abnormal. Eventually, he developed colonic perforation and had to undergo emergency surgery. An intraoperative specimen showed several microthrombi in the middle and small arteriovenous ducts of his small and large intestines. The patient’s coagulopathy improved preoperatively, and his overall condition improved postoperatively. Since the activation of ADAMTS13 was reduced remarkably, the thrombotic tendency was determined to be a thrombotic microangiopathy-like condition owing to increased vWF. We could not attribute the coagulopathy to any other cause except CMV infection; therefore, we concluded that this was a case of multiple thrombosis associated with CMV. Conclusions We present an extremely rare case of a patient with multiple thrombotic microangiopathy-like microthrombosis caused by CMV infection. Our findings suggest that CMV infection may be considered as a differential diagnosis for immunocompetent individuals who present with thrombosis of unspecified cause.